German Adjuvant Intergroup Node-positive Study (GAIN): a phase III trial comparing two dose-dense regimens (iddEPC versus ddEC-PwX) in high-risk early breast cancer patients. (28th April 2017) - Möbus, V.; von Minckwitz, G.; Jackisch, C.; Lück, H.-J.; Schneeweiss, A.; Tesch, H.; Elling, D.; Harbeck, N.; Conrad, B.; Fehm, T.; Huober, J.; Müller, V.; et al.
Abstract: Background: Dose-dense (dd) regimens are one of the preferred options for the adjuvant treatment of breast cancer patients with intermediate to high risk. The German Adjuvant Intergroup Node-positive trial aimed at optimizing intense dd (idd) strategies by evaluating drug combinations and the addition of capecitabine. Patients and methods: Women (aged 18 years and biologically <65 years) with histologically involved axillary lymph nodes were randomly assigned to receive three courses each of epirubicin (E) 150 mg/m 2, paclitaxel (P) 225 mg/m 2 and cyclophosphamide (C) 2500 mg/m 2 (reduced to 2000 mg/m 2 after recruitment of 1200 patients) q2w intravenously (i.v.) (iddEPC-regimen) or ddEC (E 112.5 mg/m 2 + C 600 mg/m 2, i.v. q2w for 4 cycles) followed by paclitaxel weekly (Pw 67.5 mg/m 2 i.v. q8d for 10 weeks) plus capecitabine (X 2000 mg/m 2 p.o. days 1–14, q22 for 4 cycles) (ddEC-PwX-regimen). Further randomization assigned patients to ibandronate for 2 years versus observation and to pegfilgrastim day 2 versus 4. Results: From June 2004 to August 2008, 2994 patients were randomized to either iddEPC ( N = 1498), or ddEC-PwX ( N = 1496) and started treatment. Median age was 50 years; pN1 (37.8%), pN2 (35.3%); pN3 (26.9%); 46.4% were G3 tumors; 76.9% hormone receptor-positive and 22% HER2-positive. After a median follow-up of 74 months, 645 events and 383 deaths were recorded. Hematological adverse events grades 3–4 were more common with iddEPC ( P < 0.001), nonhematological with ddEC-PwX ( P = 0.04), even if the toxicity profile of the two regimens was different. At 5 years, estimated disease-free survival rates for ddEC-PwX and iddEPC were 81.7% [95% confidence interval (CI) 79.5–83.6] versus 80.2% (95% CI 78.0–82.2). Hazard ratio (HR)=0.95 (95% CI 0.81–1.11, log-rank P = 0.49). Five-year overall survival rates were 89.4% for ddEC-PwX (95% CI 87.7–91.0) and 89.0% for iddEPC (95% CI 87.2–90.6), HR = 0.85 (95% CI 0.69–1.04, log-rank P = 0.10). Conclusion: Adding capecitabine to ddEC-Pw did not improve outcome in comparison to iddEPC but increased toxicity and should not be recommended for further use.